2013
DOI: 10.1016/j.jnucmat.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Advanced divertor configurations with large flux expansion

Abstract: Experimental studies of the novel snowflake divertor concept (D. Ryutov, Phys. Plasmas 14, 064502 (2007)) performed in the NSTX and TCV tokamaks are reviewed in this paper. The snowflake divertor enables power sharing between divertor strike points, as well as the divertor plasma-wetted area, effective connection length and divertor volumetric power loss to increase beyond those in the standard divertor, potentially reducing heat flux and plasma temperature at the target. It also enables higher magnetic shear Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…From the geometrical point of view the increase of the flux expansion causes an increase of the flux tube volume [29] through changes in the the parallel connection length between upstream and the target as well as an increase of the plasma-wetted area. Examples of the configuration variation from smaller to larger flux expansion are shown in Figure 3.…”
Section: Experimental Scenarios: Flux Expansion Scanmentioning
confidence: 99%
“…From the geometrical point of view the increase of the flux expansion causes an increase of the flux tube volume [29] through changes in the the parallel connection length between upstream and the target as well as an increase of the plasma-wetted area. Examples of the configuration variation from smaller to larger flux expansion are shown in Figure 3.…”
Section: Experimental Scenarios: Flux Expansion Scanmentioning
confidence: 99%
“…One recent idea for tokamak divertor is using a higher order null (dubbed "snowflake") instead of the standard x-point [1]. Snowflake divertor configuration has a characteristic hexagonal separatrix structure, and it has a number of geometric properties that may affect edge plasma and may be helpful for alleviating the divertor heat flux problem: stronger fanning of the poloidal flux, stronger magnetic shear in the edge region, larger radiating volume, and larger connection length in the scrape-off layer [2].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical considerations [3,4] and recent experimental observations from snowflake divertor experiments on several tokamaks indicate that presence of a near-second-order null of poloidal field may give rise to strong plasma mixing near the magnetic divertor null point, thereby providing sharing of heat and particle flux between multiple (three to four) strike points [5,2].…”
Section: Introductionmentioning
confidence: 99%
“…From tokamak experiments and theory [2,18] , it is found that most of is transported to the divertor target plates with a heat load width which will be less than 5mm at the outer mid-plane of HL-2M. The flux surface expansion and connection length of the snowflake divertor are much larger than that of the standard divertor, especially at the point with less than 2mm, and both of these increases are expected to reduce the heat load on the divertor target by broadening the heat load profile [19] . With the same computational boundary plasma conditions as in the standard divertor simulated above, the snowflake-minus divertor shown in figure 6 (b) is simulated by SOLPS5.0.…”
Section: Simulation Resultsmentioning
confidence: 97%
“…For DN tripod divertor configurations, constant cross-field transport factors D = 0.3m 2 /s and χ e = χ i = 1.0m 2 /s are used. When n sep =1.4×10 19 /m 3 and = 10MW, the heat load profiles on the target plates of the three divertor configurations are shown in figure 17. As the heat load profiles on the upper-inner and lower-inner targets depicted in figure 17 (a) and figure 17 (c) show, the peak heat loades are located at the point near the separatrix, but their values are less than 2.0MW/m 2 .…”
Section: Simulation Resultsmentioning
confidence: 99%